Multi-element rare earth silicate / silica carbon nano composite ceramic and preparation method thereof
The preparation of multi-component rare earth silicate/siloxocarbon nanocomposite ceramics through polymer conversion method, solving the water-oxygen corrosion problem faced by SiC/SiC ceramic matrix composites in harsh environments, and achieving excellent water resistance of ceramics at high temperatures Oxygen corrosion properties and mechanical properties.
Patent Information
- Application Number
- CN202411633054.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing SiC/SiC ceramic matrix composite materials face problems such as high temperature oxidation, water-oxygen corrosion and molten salt corrosion in harsh service environments, especially water-oxygen corrosion, which leads to structural fragility and mechanical properties degradation.
The polymer conversion method is used to prepare multivariate rare earth silicate/siloxocarbon nanocomposite ceramics. By converting the single source precursor into a multivariate rare earth silicate/siloxocarbon nanocomposite ceramic powder at high temperature, and sintered by high temperature. Prepare ceramic blocks to ensure uniform distribution of multi-element rare earth silicates and nanocrystalline structure.
It has achieved excellent anti-hydrogen corrosion performance in the range of 1200 to 1500°C, and the oxide layer is continuous and dense, which significantly improves the mechanical properties and oxidation resistance of the ceramics.
Smart Images

Figure CN119462111A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of structural ceramic materials, and in particular relates to a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic and a preparation method thereof. Background Art
[0002] Turbine engines play an extremely important role in commercial and military aircraft due to their excellent thrust / weight ratio, and are a strategic commanding height in the competition among major powers. In order to further improve the thermal efficiency and thrust of the engine, a higher turbine inlet gas temperature is required, which makes the core components such as the engine blades withstand higher temperatures and more harsh service environments. The inlet temperature of aircraft engine turbines has reached over 1600°C. Currently, single crystal high-temperature alloys with excellent comprehensive performance are mainly used to manufacture turbine blades, and thermal barrier coatings (TBCs), composite cooling, double-wall supercooling technology, etc. are applied to enable them to run at high speeds in such harsh environments. If the turbine inlet gas temperature is further increased, it will exceed the temperature resistance limit of single crystal high-temperature alloys. Even under the protection of thermal barrier coatings and a variety of cooling technologies, it is difficult to meet the demand. It is urgent to develop new high-temperature resistant turbine blade materials.
[0003] SiC / SiC ceramic matrix composites have always been one of the ideal ultra-high temperature composite materials for thermal protection components in the aerospace field due to their low density, low thermal expansion coefficient and excellent high temperature mechanical properties. Without cooling design, SiC / SiC ceramic matrix composites can not only withstand high temperatures of 1300℃ to 1600℃, but also have excellent thermal stability, which improves the efficiency of the engine and reduces fuel consumption; at the same time, the density of SiC is much lower than that of high temperature alloys, which can greatly reduce the weight of the engine. However, the service environment of engines is becoming more and more harsh nowadays, which makes SiC / SiC ceramic matrix composites have to face some severe problems: high temperature oxidation, water oxygen corrosion and molten salt corrosion; especially the problem of water oxygen corrosion. At high temperature, water vapor reacts with SiO2 protective film to form volatile hydroxides. In addition, high-speed airflow accelerates the oxidation and volatilization reaction of SiC materials, causing its structure to become fragile and its mechanical properties to degrade significantly. Not only the engine blades, but also the core components are seriously threatened.
[0004] Environmental barrier coatings (EBCs) can effectively solve the above problems by insulating water vapor. Among the many EBCs, rare earth silicates have good resistance to water vapor corrosion and are considered to be one of the most promising EBCs candidate materials. Rare earth silicates mainly include rare earth monosilicates (RE2SiO5) and rare earth disilicates (RE2Si2O7). For EBCs with single-component rare earth metal elements, if the design at higher temperatures is to be solved, the multi-component or high-entropy design of ceramics can be considered to transform them into multi-component or high-entropy ceramics (HECs). In particular, compared with their single-component compounds, HECs exhibit characteristics such as giant dielectric constants, ultrafast plasma capabilities, good catalytic properties, and excellent capacitance retention capabilities; high-entropy non-oxide materials mostly have higher hardness, low thermal conductivity, good antioxidant capacity, etc. HECs have a wide range of material systems and different properties, which can be better used in EBCs.
[0005] In recent years, in view of the excellent performance of high-entropy ceramics, people have tried to synthesize and develop high-entropy ceramics of rare earth silicates to obtain EBCs with better performance. For example, (Ho 0.25 Lu 0.25 Yb 0.25 Eu 0.25 )SiO5 powder, and studied its thermal properties, mechanical properties and matrix corrosion properties, proving the superiority of high entropy rare earth silicate ceramics as EBCs. However, it is difficult to prepare a single solid solution with a uniform distribution of multiple rare earth metal elements by solid-state reaction method, and the process is relatively complicated, which cannot meet the needs of existing EBCs. Summary of the invention
[0006] In view of the deficiencies of the prior art, the first object of the present invention is to provide a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic. The nanocomposite ceramic provided by the present invention includes powder and / or block. The nanocomposite ceramic of the present invention is made by a polymer conversion method. Compared with traditional silicon-based ceramics, the ceramics of the present invention are all nanocrystalline and have better resistance to water and oxygen corrosion; secondly, the nanocomposite ceramic of the present invention contains a multi-component rare earth silicate phase, which has excellent resistance to water and oxygen corrosion. Therefore, the nanocomposite ceramic of the present invention can make up for the poor resistance of traditional silicon-based ceramics to water and oxygen, so that it has excellent resistance to water and oxygen corrosion in the range of 1200-1500°C. It was verified through experiments that after a long period of water and oxygen (100h), it showed excellent resistance to water and oxygen corrosion.
[0007] The second object of the present invention is to provide a method for preparing multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramics. The preparation method of the present invention uses a polymer conversion ceramic method to convert a single source precursor polymer into a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder at high temperature, and prepares a nano ceramic block by high temperature sintering, wherein the average grain size of the multi-component rare earth silicate in the obtained ceramic is ≤100nm.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention discloses a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, the general composition formula of which is (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 / SiOC, wherein 0≤a<1, 0≤b<1, 0≤c<1, 0≤d<1, 0≤e<1, 0≤f<1, 0≤g<1, 0≤h<1, 0≤i<1, 0≤j<1, a+b+c+d+e+f+g+h+i+j=1, and at least 2 of a, b, c, d, e, f, g, h, i, j are not 0 at the same time, x=1 or 2, in the polynary rare earth silicate, the rare earth metal elements share the cation lattice sites of the crystal to form a single solid solution.
[0010] The nanocomposite ceramic provided by the present invention is a composite ceramic in which at least two of a, b, c, d, e, f, g, h, i, and j are not simultaneously zero, that is, a polynary rare earth silicate (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 There are at least two kinds of metal elements.
[0011] Preferably, the nanocomposite ceramic contains uniformly distributed multi-component rare earth silicate phase and SiOC ceramic phase.
[0012] As a preferred embodiment, the general formula (Yb a Ho b Er c Lud Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 The multi-component rare earth silicate in / SiOC has a monoclinic crystal structure. The rare earth metal elements Yb, Ho, Er, Lu, Tm, Gd, Tb, Y, La, and Sc atoms share the cation lattice sites of the crystal, and Si and O atoms occupy the anion lattice sites to form a single solid solution.
[0013] As a preferred embodiment, polynary rare earth silicate (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 The metal elements in the mixture may be in equal molar ratio or non-equal molar ratio. In the present invention, the metal elements in equal molar ratio or nearly equal molar ratio are medium entropy or high entropy rare earth silicates.
[0014] Preferably, the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic of the present invention is a ceramic powder and / or a ceramic block, the particle size of the ceramic powder is 0.1μm-1000μm, more preferably 5μm-200μm, and the porosity of the ceramic block is 0%-30%, more preferably 0%-10%.
[0015] Preferably, in the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic of the present invention, the average grain size of at least one phase in the nanocomposite ceramic is 0.1nm-100nm; more preferably 1nm-70nm.
[0016] As a preferred embodiment, the present invention provides a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, multi-component rare earth silicate (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 The mass fraction is 0.1%-95%, more preferably 20%-85%.
[0017] The present invention provides a method for preparing a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, comprising the following steps:
[0018] (1) weighing and mixing a complex of at least two metal elements selected from Yb, Ho, Er, Lu, Tm, Gd, Tb, Y, La, and Sc and a silicon-based polymer according to a stoichiometric ratio to obtain a chemical raw material, dissolving the prepared chemical raw material in an organic solvent in an inert atmosphere, stirring and mixing the mixture, and then heating the mixture to cause a chemical reaction, thereby connecting the metal atoms to the silicon-based polymer molecular chain through chemical bonds, and finally removing the solvent to obtain a silicon-based single-source precursor containing at least two rare earth metal elements at the same time;
[0019] (2) crosslinking and high-temperature heat treatment of the silicon-based single-source precursor obtained in step (1) under an inert atmosphere to complete the "polymer-ceramic" conversion and phase separation and crystallization process, thereby obtaining a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, wherein the inert gas is argon or nitrogen, the crosslinking temperature is 150-300° C., the heat treatment temperature is 1100-1800° C., preferably 1400-2200° C., and the holding time at the highest temperature is 0.1-20 h;
[0020] or
[0021] The silicon-based single-source precursor obtained in step (1) is cross-linked and pyrolyzed under an inert atmosphere to complete the "polymer-ceramic" conversion process, thereby obtaining a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder; the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder is subjected to high-temperature sintering to obtain a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block, wherein the pyrolysis temperature is 800-1500°C, preferably 800-1300°C, and the high-temperature sintering conditions are: the vacuum degree of the sintering furnace is less than 35Pa, preferably 5Pa, the sintering temperature is 1000-2000°C, preferably 1500-2200°C, the sintering pressure is 0-150MPa, the holding time is 0-600min, and the heating rate is 5-800°C / min.
[0022] As a preferred embodiment; the Yb metal element complex is selected from ytterbium acetate (III) [C6H9O6Yb], ytterbium chloride (III) [YbCl3], ytterbium acetylacetonate (III) [C 15 H 21 O6Yb], ytterbium(III)nitrate[Yb(NO3)3], ytterbium(III)carbonate[C3H2O 10 At least one of Yb2], ytterbium (III) fluoride [F3Yb] and hydrates thereof. Of course, other Yb metal element complexes can also be used in the present invention.
[0023] As a preferred embodiment; the metal element complex of Ho is selected from holmium acetate (III) [(CH3CO2) 3Ho], holmium chloride (III) [HoCl3], holmium acetylacetonate (III) [C 15 H 21 At least one of holmium (III) [C3O9Ho2], holmium (III) fluoride [F3Ho] and hydrates thereof. Of course, other Ho metal element complexes can also be used in the present invention.
[0024] As a preferred embodiment; the Er metal element complex is selected from erbium acetate (III) [(CH3CO2) 3Er], erbium chloride (III) [ErCl3], erbium acetylacetonate (III) [C 15 H 21 At least one of Er(III)[Er(O6Er], Er(III)[Er(NO3)3], Er(III)[C3O9Er2], Er(III)[F3Er] and their hydrates. Of course, other Er metal element complexes can also be used in the present invention.
[0025] As a preferred embodiment; the complex of the Lu metal element is selected from lutetium acetate (III) [(CH3CO2) 3Lu], lutetium chloride (III) [LuCl3], lutetium acetylacetonate (III) [C 15 H 21 O6Lu], lutetium(III) nitrate [Lu(NO3)3] or lutetium(III) carbonate hydrate [C3H2O 10 At least one of Lu2], lutetium (III) fluoride [F3Lu] and hydrates thereof. Of course, other Lu metal element complexes can also be used in the present invention.
[0026] As a preferred embodiment; the complex of the Tm metal element is selected from thulium acetate (III) [Tm (OOCCH3) 3], thulium chloride (III) [TmCl3], thulium acetylacetonate (III) [C 15 H 21 At least one of thulium (III) nitrate [Tm(NO3)3], thulium (III) carbonate hydrate [C3O9Tm2], thulium (III) fluoride [F3Tm] and hydrates thereof. Of course, other Tm metal element complexes can also be used in the present invention.
[0027] As a preferred embodiment; the complex of the Gd metal element is selected from gadolinium acetate (III) [Gd(CH3CO2)3], gadolinium chloride (III) [GdCl3], gadolinium acetylacetonate (III) [C 15 H 21At least one of gadolinium (III) [Gd(O6Gd], gadolinium (III) nitrate [Gd(NO3)3], gadolinium (III) carbonate [C3O9Gd2], gadolinium (III) fluoride [F3Gd] and their hydrates. Of course, other Gd metal element complexes can also be used in the present invention.
[0028] As a preferred embodiment; the complex of the Tb metal element is selected from terbium acetate (III) [C6H9O6Tb], terbium chloride (III) [TbCl3], terbium acetylacetonate (III) [C 15 H 21 At least one of terbium (III) nitrate [Tb(NO3)3], terbium (III) carbonate [C3O9Tb2], terbium (III) fluoride [F3Tb] and hydrates thereof. Of course, other Tb metal element complexes can also be used in the present invention.
[0029] As a preferred embodiment; the complex of the metal element Y is selected from yttrium acetate (III) [C6H9O6Y], yttrium chloride (III) [YCl3], yttrium acetylacetonate (III) [C 15 H 21 At least one of yttrium (III) [C3O6Y], yttrium (III) nitrate [Y(NO3)3], yttrium (III) carbonate [C3O9Y2], yttrium (III) fluoride [F3Y] and hydrates thereof. Of course, other Y metal element complexes can also be used in the present invention.
[0030] As a preferred embodiment; the complex of the La metal element is selected from lanthanum acetate (III) [C6H9O6La], lanthanum chloride (III) [LaCl3], lanthanum acetylacetonate (III) [C 15 H 21 O6La], lanthanum (III) nitrate [La(NO3)3], lanthanum (III) carbonate [C3O9La2], lanthanum (III) fluoride [F3La] and at least one of their hydrates; of course, other La metal element complexes can also be used in the present invention.
[0031] As a preferred embodiment; the complex of the Sc metal element is selected from scandium acetate (III) [C6H9O6Sc], scandium chloride (III) [ScCl3], acetylacetonate scandium (III) [C 15 H 21 At least one of scandium (III) nitrate [Sc(NO3)3], scandium (III) carbonate [C3O9Sc2], scandium (III) fluoride [F3Sc] and their hydrates; of course, other Sc metal element complexes can also be used in the present invention.
[0032] As a preferred embodiment, the silicon-based polymer is one or more of polysiloxane, polycarbosilane, allyl hydrogenated polycarbosilane, vinyl polycarbosilane, and hyperbranched polycarbosilane, preferably polysiloxane. When the silicon-based polymer is preferably polysiloxane, the final composite ceramic has the best performance.
[0033] In the present invention, the preferred rare earth metal element complex reacts with a portion of the silicon-based polymer to form a multi-component rare earth silicate phase, while the other portion of the silicon-based polymer is pyrolyzed to form a SiOC phase, thereby forming a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, that is, the general chemical composition formula: (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 / SiOC.
[0034] As a preferred embodiment, the organic solvent is at least one of anhydrous isopropanol or anhydrous xylene.
[0035] As a preferred embodiment, the inert atmosphere is argon and / or nitrogen.
[0036] As a preferred embodiment, the heating temperature is 30-200°C, more preferably 80-150°C, and the heating reaction time is 10-600min, more preferably 120-180min.
[0037] The solvent removal method is vacuum distillation or rotary evaporation. Preferably, the solvent removal adopts vacuum distillation, and the heating temperature range during vacuum distillation is 50-80° C. After the solvent is removed, a silicon-based single-source precursor containing at least two rare earth metal elements is obtained.
[0038] As a further preferred embodiment, the pyrolysis temperature is 800-1500°C and the insulation time is 2-4h.
[0039] The present invention heat treats the obtained silicon-based single-source precursor at a higher temperature (≥1200° C.) under the protection of inert gas to obtain multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramics.
[0040] Preferably, the heat treatment temperature is 1300-1800°C and the insulation time is 2-6h.
[0041] The multi-component rare earth silicate / silicon oxygen carbon nano-composite ceramic powder obtained by the invention is subjected to high-temperature sintering to obtain a multi-component rare earth silicate / silicon oxygen carbon nano-composite ceramic block.
[0042] As a preferred embodiment, the high temperature sintering is spark plasma sintering, and the sintering conditions are: sintering furnace vacuum degree <5Pa, temperature 1000-2000°C, sintering pressure 50-100MPa, holding time 10-30min, heating rate 100-800°C / min, preferably 100-400°C / min.
[0043] The average grain size of the multi-component rare earth silicate / silicon oxygen carbon nano-composite ceramic block obtained by the present invention is less than 100nm, and can be less than or equal to 60nm after optimization.
[0044] The mass of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block obtained by the present invention has been increasing under the condition of water and oxygen at 1200°C, and its parabolic oxidation rate constant (K p ) is less than 8.0*10 -1 mg 2 / (cm 4 ·h). The parabolic oxidation rate constant (K p ) is less than 7.0*10 -1 mg 2 / (cm 4 ·h). Under 1500℃ water-oxygen conditions, the mass of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block first increases and then decreases, and the parabolic oxidation rate constant in the decreasing stage is less than -3.0*10 -2 mg 2 / (cm 4 ·h). The parabolic oxidation rate constant (K p ) is less than -2.0*10 -2 mg 2 / (cm 4 ·h). Compared with pure SiOC ceramics, its linear oxidation rate constant (K p ) is 4.677*10 -1 mg 2 / (cm 4 ·h). The parabolic oxidation rate constant (K p ) is -2.078*10 -1 mg 2 / (cm 4 h). Under the same conditions, the water-oxygen corrosion resistance of the multi-component rare earth silicate / silicon-oxygen-carbon nanocomposite ceramic block is better than that of pure SiOC ceramic.
[0045] The technical solution of the present invention has the following advantages:
[0046] (1) The preparation process of the method of the present invention is simple and easy to implement, and the preparation cycle is short;
[0047] (2) The method of the present invention is conducive to achieving flexible regulation and uniform distribution of metal elements at the molecular level;
[0048] (3) The ceramic prepared by the present invention has good water and oxygen resistance. The obtained nanocomposite ceramic block has excellent water and oxygen corrosion resistance at 1200-1500°C, and the oxide layer is continuous and dense.
[0049] This method introduces rare earth metal elements through the chemical reaction of small molecules of the complex and polymers, and can achieve precise control of the types and contents of multiple rare earth metal elements through the types and proportions of the complexes, and can achieve uniform mixing of rare earth metal elements at the molecular level, which can effectively solve the problems of forming a single-phase solid solution of multiple elements, uniform distribution of nano-ceramic phases and high-temperature grain coarsening, thereby improving the mechanical properties and antioxidant properties of the material. This method has the advantages of simple equipment, simple and reliable process, short preparation cycle, and potential for large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a process flow chart for preparing multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramics of the present invention.
[0051] Figure 2 This is the XRD spectrum of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder obtained in Example 1 of the present invention.
[0052] Figure 3 This is the XRD spectrum of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder obtained in Example 2 of the present invention.
[0053] Figure 4 This is the XRD spectrum of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder obtained in Example 3 of the present invention.
[0054] Figure 5 This is the XRD spectrum of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder obtained in Example 4 of the present invention.
[0055] Figure 6 This is a TEM image of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder obtained in Example 4 of the present invention.
[0056] Figure 7 This is the XRD spectrum of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block obtained in Example 5 of the present invention.
[0057] Figure 8 This is a cross-sectional SEM image of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block obtained in Example 5 of the present invention after water oxidation at 1200°C.
[0058] Fig. 9 This is a surface SEM comparison of the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block obtained in Example 5 of the present invention and the ordinary SiOC ceramic block after water oxidation at 1300°C.
[0059] Fig.10 This is the XRD spectrum of the ceramic powder obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0060] The present invention is further described below by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0061] Example 1
[0062] According to (Tm 0.2 Yb 0.3 Er 0.3 Ho 0.3 )2SiO5 stoichiometric ratio: 1g of ytterbium (III) acetate tetrahydrate, 0.82g of thulium (III) acetate hydrate, 0.83g of erbium (III) acetate tetrahydrate, and 0.81g of holmium (III) acetate hydrate were weighed and dissolved in anhydrous isopropanol, 3.32g of polysiloxane (PSO) was weighed, the two were mixed evenly, stirred at room temperature for 30min, heated to 150°C and kept warm for 2h, cooled naturally and allowed to stand, isopropanol was removed by reduced pressure distillation, and then placed in 250°C for cross-linking, and the single-source precursor was kept warm at 1100°C in argon for 3h to obtain ceramic powder, which was then heat-treated at 1300°C, 1400°C, and 1500°C in argon for 2h to obtain crystallized ceramics.
[0063] like Figure 2 As shown, the chemical composition is (Tm 0.2 Yb 0.3 Er 0.3 Ho 0.3 )2SiO5 / SiOC ceramics, its XRD spectrum shows two groups of diffraction peaks, among which the main peak is the diffraction peak of rare earth silicate with monoclinic crystal structure, that is: there are two equal Tm, Yb, Er, Ho atoms occupying the cation sites, on the first Tm, Yb, Er, Ho site, Tm, Yb, Er, Ho and 7 O 2- The atoms combine to form a distorted (Tm, Yb, Er, Ho)O7 hexagonal pyramid, which shares its corners with two equivalent SiO4 tetrahedrons, and its corners are shared with 6 equivalent (Tm, Yb, Er, Ho)O7 hexagonal pyramids, and its corners are shared with one SiO4 tetrahedron. In the second Tm, Yb, Er, Ho position, Tm, Yb, Er, Ho and 8 O 2-atoms combine. Si and O atoms occupy the anion lattice sites and combine to form SiO4 tetrahedrons to form a solid solution. The secondary peak is a small amount of SiC diffraction peak.
[0064] The XRD refinement calculation shows that the (Tm 0.2 Yb 0.3 Er 0.3 Ho 0.3 )2SiO5 crystal grain size is 1.55nm, (Tm 0.2 Yb 0.3 Er 0.3 Ho 0.3 )The unit cell parameters of 2SiO5 are a=0.66333nm, b=0.68231nm, c=0,89909nm.
[0065] Example 2
[0066] According to (Tm 0.2 Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 )2SiO5 stoichiometric ratio: 1.05 g of ytterbium (III) tetrahydrate, 0.82 g of thulium (III) acetate hydrate, 0.82 g of erbium (III) acetate tetrahydrate, 0.82 g of holmium (III) acetate hydrate, and 0.85 g of lutetium (III) acetate hydrate were weighed and dissolved in anhydrous isopropanol, 4.2 g of PSO was weighed, the two were mixed evenly, stirred at room temperature for 30 min, and then heated to 150°C and kept warm for 2 h. After natural cooling, it was allowed to stand, and the isopropanol was distilled off under reduced pressure. It was then placed in 250°C for cross-linking, and the single-source precursor was kept warm at 1100°C in argon for 3 h to obtain ceramic powder, which was then heat-treated at 1300°C, 1400°C, and 1500°C in argon for 2 h.
[0067] like Figure 3 As shown, the chemical composition is (Tm 0.2 Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 )2SiO5 / SiOC nanoceramics, its XRD spectrum shows two groups of diffraction peaks, which are typical diffraction peaks of rare earth metal silicates with monoclinic crystal structure, that is, there are two equal Tm, Yb, Er, Ho, Lu atoms occupying the cation sites, on the first Tm, Yb, Er, Ho, Lu site, Tm, Yb, Er, Ho, Lu and 7 O 2- atoms combine to form a distorted (Tm, Yb, Er, Ho, Lu)O7 hexagonal pyramid, which shares its corners with two equivalent SiO4 tetrahedrons, and its corners are shared with 6 equivalent (Tm, Yb, Er, Ho, Lu)O7 hexagonal pyramids, and its corners are shared with one SiO4 tetrahedron. In the second Tm, Yb, Er, Ho, Lu position, Tm, Yb, Er, Ho, Lu and 8 O 2 -Atoms combine. Si and O atoms occupy the anion lattice sites and combine to form SiO4 tetrahedrons, thus forming a solid solution.
[0068] The Tm 0.15 Yb 0.25 Er 0.2 Ho 0.2 Lu 0.2 )2SiO5 crystal grain size is 1.46nm, (Tm 0.15 Yb 0.25 Er 0.2 Ho 0.2 Lu 0.2 )The unit cell parameters of 2SiO5 are a=0.66452nm, b=0.68043nm, c=0.8993nm.
[0069] Example 3
[0070] According to (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 G 0.2 )2SiO5 stoichiometric ratio: weigh 1g of ytterbium (III) acetate tetrahydrate, 0.94g of gadolinium (III) acetate hydrate, 0.93g of erbium (III) acetate tetrahydrate, 0.96g of holmium (III) acetate hydrate, and 0.94g of lutetium (III) acetate hydrate, and dissolve them in anhydrous isopropanol; weigh 4.13g of PSO, mix the two evenly, stir at room temperature for 30min, heat to 150℃ and keep warm for 2h, cool naturally and still, distill under reduced pressure to remove anhydrous isopropanol, then put it into 250℃ for cross-linking, and then keep the single-source precursor at 1100℃ in argon for 3h to obtain ceramic powder, which is then heat-treated at 1300℃, 1400℃ and 1500℃ in argon for 2h.
[0071] like Figure 4 As shown, the chemical composition is (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 G 0.2)2SiO5 / SiOC ceramic powder, its XRD spectrum shows two groups of diffraction peaks, which are typical diffraction peaks of rare earth metal silicates with monoclinic crystal structure, that is: there are two equal Lu, Yb, Er, Ho, Gd atoms occupying the cation sites, on the first Lu, Yb, Er, Ho, Gd site, Lu, Yb, Er, Ho, Gd and 7 O 2 - atoms combine to form a distorted (Lu, Yb, Er, Ho, Gd)O7 hexagonal pyramid, which shares its corners with two equivalent SiO4 tetrahedrons, and its corners are shared with 6 equivalent (Lu, Yb, Er, Ho, Gd)O7 hexagonal pyramids, and its corners are shared with one SiO4 tetrahedron. In the second Lu, Yb, Er, Ho, Gd position, Lu, Yb, Er, Ho, Gd and 8 O 2 -Atoms combine. Si and O atoms occupy the anion lattice sites and combine to form SiO4 tetrahedrons, thus forming a solid solution.
[0072] Calculated (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 G 0.2 )2SiO5 rare earth sodium silicate crystal size is 1.31nm, (Yb 0.22 Er 0.2 Ho 0.2 Lu 0.2 G 0.18 )The unit cell parameters of 2SiO5 are a=0.66425nm, b=0.68137nm, c=0.90089nm.
[0073] Example 4
[0074] According to (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 stoichiometric ratio: 1.01g of ytterbium (III) acetate tetrahydrate, 1.02g of hydrated terbium (III) acetate, 1.02g of erbium (III) acetate tetrahydrate, 1.04g of holmium (III) acetate hydrate and 1.02g of lutetium (III) acetate hydrate were weighed and dissolved in anhydrous isopropanol, 4.52g of PSO was weighed, the two were mixed evenly, stirred at room temperature for 30min, heated to 150℃ and kept warm for 2h, cooled and allowed to stand naturally, and the anhydrous isopropanol solution was removed by reduced pressure distillation, and then placed in 250℃ for cross-linking, and the single-source precursor was kept warm at 1100℃ in argon for 3h to obtain ceramic powder, which was then heat-treated at 1300℃, 1400℃ and 1500℃ in argon for 2h.
[0075] Through the elemental analysis results, it was calculated that the contents of Yb, Ho, Er, Lu, and Tb were approximately equal in molar ratio, that is, the chemical composition was (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 / SiOC nanoceramics. Figure 5 As shown, its XRD spectrum shows two groups of diffraction peaks, which are typical diffraction peaks of rare earth metal silicates with monoclinic crystal structure, that is, there are two equal Lu, Yb, Er, Ho, Tb atoms occupying the cation sites. On the first Lu, Yb, Er, Ho, Tb site, Lu, Yb, Er, Ho, Tb and 7 O 2 -atoms combine to form a distorted (Lu, Yb, Er, Ho, Tb)O7 hexagonal pyramid, which shares its corners with two equivalent SiO4 tetrahedrons, and its corners are shared with 6 equivalent (Lu, Yb, Er, Ho, Tb)O7 hexagonal pyramids, and its corners are shared with one SiO4 tetrahedron. In the second Lu, Yb, Er, Ho, Tb position, Lu, Yb, Er, Ho, Tb and 8 O 2 -Atoms combine. Si and O atoms occupy the anion lattice sites and combine to form SiO4 tetrahedrons, thus forming a solid solution.
[0076] Calculated (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 crystal grain size is 1.37nm, such as Figure 6 As shown in (a), the rare earth silicates obtained are almost uniform (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5, Figure 6 (b) Statistics (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 grain size is about 3.61nm, which is close to the XRD refinement result. Figure 6 (c) shows that the various metal elements in rare earth silicates are evenly distributed. 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2)The unit cell parameters of 2SiO5 are a=0.66437nm, b=0.68209nm, c=0.90087nm.
[0077] Example 5
[0078] According to (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5: 3.06 g of ytterbium (III) acetate tetrahydrate, 3.05 g of hydrated terbium (III) acetate, 3.07 g of erbium (III) acetate tetrahydrate, 3.05 g of holmium (III) acetate hydrate and 3.06 g of lutetium (III) acetate hydrate were weighed and dissolved in anhydrous isopropanol, 14.09 g of PSO was weighed, the two were mixed evenly, stirred at room temperature for 30 min, heated to 150°C and kept warm for 2 h, cooled and allowed to stand naturally, and the anhydrous isopropanol solution was removed by reduced pressure distillation, and then it was placed in 250°C for cross-linking, and the single-source precursor was kept warm at 1100°C in argon for 3 h to obtain ceramic powder.
[0079] The ceramic powder was placed in a graphite mold for spark plasma sintering. The vacuum degree in the furnace was less than 5 Pa. The temperature was raised to 1500°C at a heating rate of 100°C / min, kept for 20 minutes, and the pressure was 50 MPa. It was then cooled to room temperature at a cooling rate of 100°C / min to obtain a nanoceramic block, recorded as (YbErHoLuTb)2SiO5-SPS.
[0080] like Figure 7 As shown, the chemical composition is (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 / SiOC and (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2Si2O7 / SiOC ceramic block, its density is 93.85%, its XRD spectrum shows two groups of diffraction peaks, (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 is a typical rare earth metal silicate diffraction peak with a monoclinic crystal structure, that is, there are two equal Lu, Yb, Er, Ho, Tb atoms occupying the cation site. On the first Lu, Yb, Er, Ho, Tb site, Lu, Yb, Er, Ho, Tb and 7 O 2-atoms combine to form a distorted (Lu, Yb, Er, Ho, Tb)O7 hexagonal pyramid, which shares its corners with two equivalent SiO4 tetrahedrons, and its corners are shared with 6 equivalent (Lu, Yb, Er, Ho, Tb)O7 hexagonal pyramids, and its corners are shared with one SiO4 tetrahedron. In the second Lu, Yb, Er, Ho, Tb position, Lu, Yb, Er, Ho, Tb and 8 O 2 -atoms combine. Si and O atoms occupy the anion lattice points and combine to form SiO4 tetrahedrons, thus forming a solid solution. (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2Si2O7 is a typical rare earth metal silicate diffraction peak with a triclinic crystal structure, that is, there are four unequal Lu, Yb, Er, Ho, Tb atoms occupying the cation sites. At the first site of Lu, Yb, Er, Ho, Tb, Lu, Yb, Er, Ho, Tb are in a 7-coordinate geometric form with 7 O 2 - atoms are combined, and in the second position of Lu, Yb, Er, Ho, Tb, Lu, Yb, Er, Ho, Tb are combined with 8 O in the form of 8-coordinate geometry. 2 - atoms bonded to the third Lu, Yb, Er, Ho, Tb sites, Lu, Yb, Er, Ho, Tb and 6 O 2 - atoms combine to form (Lu, Yb, Er, Ho, Tb)O6 octahedron, which shares corners with 7 SiO4 tetrahedrons. At the fourth site of Lu, Yb, Er, Ho, Tb, Lu, Yb, Er, Ho, Tb are combined with 8 O in the form of 8-coordinate geometry. 2 - atoms combine, Si and O atoms occupy the anion lattice sites, and combine to form SiO4 tetrahedrons, thus forming a solid solution.
[0081] The calculated ceramic block (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 rare earth silicate crystal grain size is 2.64nm, (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )2SiO5 unit cell parameters are a=0.66502nm,b=0.68107nm,c=0.89987nm;(Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb0.2 )2Si2O7 rare earth silicate crystal grain size is 1.43nm, (Yb 0.2 Er 0.2 Ho 0.2 Lu 0.2 Tb 0.2 )The unit cell parameters of 2Si2O7 are a=0.65274nm, b=0.65543nm, c=1.2008nm.
[0082] Figure 8 This is the cross-sectional view of (YbErHoLuTb)2SiO5-SPS after water-oxygen corrosion at 1200℃ for 50h. The water-oxygen layer in the figure is continuous and dense, with a thickness of about 7.11μm. Its mass has been on an upward trend. The parabolic oxidation rate constant (K p ) is 6.245*10 -1 mg 2 / (cm 4 ·h). The ceramic mass during water-oxygen corrosion at 1500℃ first increases and then decreases. The parabolic oxidation rate constant (K p ) is -5.13*10 -2 mg 2 / (cm 4 ·h). For pure SiOC ceramics, the physical oxidation rate constant (K p ) is 4.677*10 -1 mg 2 / (cm 4 h), the parabolic oxidation rate constant (K p ) is -2.078*10 -1 mg 2 / (cm 4 h). Compared with SiOC, its water and oxygen corrosion resistance has been significantly improved.
[0083] Fig. 9 The following are the surface images of (YbErHoLuTb)2SiO5-SPS and SiOC ceramics after 100h of water-oxygen corrosion at 1300℃. Figure a is (YbErHoLuTb)2SiO5-SPS and Figure b is SiOC ceramics. It can be clearly seen from the figure that the surface of (YbErHoLuTb)2SiO5-SPS in Figure a is dense and crack-free, while the surface of SiOC ceramic in Figure b has many cracks, and the ceramic surface has already fallen off significantly. Compared with SiOC ceramics and a number of ordinary silicon-based ceramics, the resistance of (YbErHoLuTb)2SiO5-SPS to water-oxygen corrosion is excellent.
[0084] Comparative Example 1
[0085] According to the stoichiometric ratio of Yb2SiO5, 5g of ytterbium acetate (III) tetrahydrate was weighed and dissolved in anhydrous isopropanol, and 5g of PSO was weighed and dissolved in anhydrous isopropanol. The two were mixed evenly, heated to 150°C for 2h, cooled naturally, and anhydrous isopropanol was removed by vacuum distillation. Then, it was placed in 250°C for cross-linking, and the single-source precursor was kept at 1100°C in argon for 3h to obtain ceramic powder. Subsequently, it was heat treated at 1300-1500°C in argon for 2h.
[0086] like Fig.10 As shown in the figure, the prepared ceramic powder exhibits multiple characteristic peaks, indicating that when there is only one rare earth metal element in the rare earth silicate, the ceramic powder obtained after heat treatment or pyrolysis cannot form a single stable rare earth silicate ceramic. When the temperature is lower than 1100°C, it is Yb2SiO5 phase, and when the temperature is higher than 1300°C, it is Yb2SiO5 and Yb2Si2O7 phase. However, if it is the previous high entropy rare earth silicate, its phase is a single phase.
[0087] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, characterized in that: The composition formula of the rare earth silicate ceramic is (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 / SiOC, wherein 0≤a<1, 0≤b<1, 0≤c<1, 0≤d<1, 0≤e<1, 0≤f<1, 0≤g<1, 0≤h<1, 0≤i<1, 0≤j<1, a+b+c+d+e+f+g+h+i+j=1, and at least 2 of a, b, c, d, e, f, g, h, i, j are not 0 at the same time, and x=1 or 2.
2. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: The nano composite ceramic contains uniformly distributed multi-component rare earth silicate phase and SiOC ceramic phase.
3. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: General formula (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 The multi-component rare earth silicates in / SiOC have a monoclinic crystal structure. The rare earth metal elements Yb, Ho, Er, Lu, Tm, Gd, Tb, Y, La, and Sc atoms share the cation lattice sites of the crystal, and Si and O atoms occupy the anion lattice sites to form a single solid solution.
4. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: Multi-component rare earth silicate (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 The metal elements in the solution may be in an equimolar ratio or a unequal molar ratio.
5. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: Multi-component rare earth silicate (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 There are at least two kinds of rare earth metal elements.
6. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: The nanocomposite ceramic can be a ceramic powder or a ceramic block. The particle size of the ceramic powder is 0.1 μm-1000 μm, and the open porosity of the ceramic block is 0%-30%.
7. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: The average grain size of at least one phase in the nanocomposite ceramic is 0.1nm-100nm.
8. The multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 1, characterized in that: In the nanocomposite ceramic, the multi-component rare earth silicate (Yb a Ho b Er c Lu d Tm e G f Tb g Y h La i Sc j )2Si x O 2x+3 The mass fraction is 0.1%-95%.
9. A method for preparing the multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to any one of claims 1 to 8, characterized in that: The steps include: (1) weighing and mixing a complex of at least two metal elements selected from Yb, Ho, Er, Lu, Tm, Gd, Tb, Y, La, and Sc and a silicon-based polymer according to a stoichiometric ratio to obtain a chemical raw material, dissolving the prepared chemical raw material in a solvent in an inert atmosphere, stirring and mixing the mixture, and then heating the mixture to cause a chemical reaction, thereby connecting the rare earth metal atoms to the silicon-based polymer molecular chain through chemical bonds, and finally removing the solvent to obtain a silicon-based single-source precursor containing at least two rare earth metal elements at the same time; (2) crosslinking and high-temperature heat treatment of the silicon-based single-source precursor obtained in step (1) under an inert atmosphere to complete the "polymer-ceramic" conversion and phase separation and crystallization process to obtain a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic, wherein the inert gas is argon or nitrogen, the crosslinking temperature is 150-300°C, the heat treatment temperature is 1100-1800°C, and the holding time at the highest temperature is 0.1-20h; or The silicon-based single-source precursor obtained in step (1) is cross-linked and pyrolyzed under an inert atmosphere to complete the "polymer-ceramic" conversion process, thereby obtaining a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic powder; the ceramic powder is subjected to high-temperature sintering to obtain a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic block, wherein the pyrolysis temperature is 800-1500°C, and the high-temperature sintering conditions are: sintering furnace vacuum degree <35Pa, sintering temperature 1000-2000°C, sintering pressure 0-150MPa, holding time 0-600min, and heating rate 5-800°C / min.
10. The method for preparing a multi-component rare earth silicate / silicon oxygen carbon nanocomposite ceramic according to claim 9, characterized in that: The Yb element complex is at least one selected from ytterbium (III) acetate, ytterbium (III) chloride, ytterbium (III) acetylacetonate, ytterbium (III) nitrate, ytterbium (III) carbonate or ytterbium (III) fluoride and hydrates thereof; The Ho element complex is selected from at least one of holmium (III) acetate, holmium (III) chloride, holmium (III) acetylacetonate, holmium (III) nitrate, holmium (III) carbonate or holmium (III) fluoride and hydrates thereof; The Er metal element complex is at least one selected from erbium (III) acetate, erbium (III) chloride, erbium (III) acetylacetonate, erbium (III) nitrate, erbium (III) carbonate, erbium (III) fluoride and hydrates thereof; The Lu metal element complex is at least one selected from lutetium (III) acetate, lutetium (III) chloride, lutetium (III) acetylacetonate, lutetium (III) nitrate, lutetium (III) carbonate, lutetium (III) fluoride and hydrates thereof; The Tm metal element complex is at least one selected from thulium (III) acetate, thulium (III) chloride, thulium (III) acetylacetonate, thulium (III) nitrate, thulium (III) carbonate, thulium (III) fluoride and hydrates thereof; The Gd metal element complex is at least one selected from gadolinium (III) acetate, gadolinium (III) chloride, gadolinium (III) acetylacetonate, gadolinium (III) nitrate, gadolinium (III) carbonate, gadolinium (III) fluoride and hydrates thereof; The Tb metal element complex is at least one selected from terbium (III) acetate, terbium (III) chloride, terbium (III) acetylacetonate, terbium (III) nitrate, terbium (III) carbonate, terbium (III) fluoride and hydrates thereof; The Y metal element complex is at least one selected from yttrium (III) acetate, yttrium (III) chloride, yttrium (III) acetylacetonate, yttrium (III) nitrate, yttrium (III) carbonate, yttrium (III) fluoride and hydrates thereof; The La metal element complex is at least one selected from lanthanum (III) acetate, lanthanum (III) chloride, lanthanum (III) acetylacetonate, lanthanum (III) nitrate, lanthanum (III) carbonate, lanthanum (III) fluoride and hydrates thereof; The Sc metal element complex is at least one selected from scandium (III) acetate, scandium (III) chloride, scandium (III) acetylacetonate, scandium (III) nitrate, scandium (III) carbonate, scandium (III) fluoride and hydrates thereof; The silicon-based polymer is one or more of polysiloxane, polycarbosilane, allyl hydrogenated polycarbosilane, vinyl polycarbosilane, and hyperbranched polycarbosilane; the organic solvent is anhydrous isopropanol or anhydrous xylene; the inert atmosphere is argon and / or nitrogen; the heating temperature is 30-200° C.; the heating reaction time is 10-600 min; and the solvent removal method is vacuum distillation or rotary evaporation; The high temperature sintering is spark plasma sintering, and the sintering conditions are: sintering furnace vacuum degree <35Pa, temperature 1000-2000°C, sintering pressure 50-100MPa, insulation time 10-30min, heating rate 100-800°C / min.
Citation Information
Patent Citations
Preparation method of high strength porous silicon carbide ceramics
CN109534816A
SiYOC ceramic material and preparation method thereof
CN111747746A
Multiphase coupling low-temperature preparation method of ultrahigh-temperature ceramic coating
CN112250443A
Multi-component carbide / silicon carbide nano composite ceramic and preparation method thereof
CN115180950A
In-situ reaction polymer converted Sc2Si2O7-SiOC composite ceramic and preparation method thereof
CN115231911A
Cited By
Non-equal-ratio ternary rare earth disilicate environmental barrier coating and high-energy plasma preparation method thereof
CN121044899A
Method for preparing ceramic-based composite material through ultra-fast infiltration and pyrolysis and application of ceramic-based composite material
CN121426582A